The 32 kDa Outer Membrane Proteins of Klebsiella pneumoniae Acts as A Bacterial Adhesin - Agustina, Dini; Shodikin, M. Ali; Nugraha, Bima Setia Sandya; Mufida, Diana Chusna; Suswati, Enny; Hermansyah, Bagus (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2022)
Klebsiella pneumoniae is a bacterium that often causes infection in the human body. At present K. pneumoniae can resist some of the antibiotics it has associated with modification of one of the virulence factors possessed by K. pneumoniae. One virulence factor of K. pneumoniae as pathogen bacteria is Outer Membrane Protein (OMP). The study of adhesin factors in K. pneumoniae involving hemagglutinin and adhesin proteins that have been found in the OMP 20 kDa and 40 kDa, but there is still no research that discusses the role of 32 kDa OMP as a hemagglutinin protein and adhesin. The purpose of this study is to determine the role of 32 kDa outer membrane of K. pneumoniae as hemagglutinin and adhesin proteins. After isolation of Outer Member Protein (OMP) from the K. pneumoniae, which then carried out a hemagglutination test using mice erythrocyte cells and adhesion test using mice enterocyte cells. The results of the hemagglutination test using mice erythrocyte cells obtained the highest hemagglutination titer for the molecular weight of 32 kDa in titers 1/4. The adhesion index with dilution titer has a significant relationship, with a conversion coefficient of 0,813 which means the dilution titer with the OMP adhesion index has a strong relationship with the direction of a positive relationship. The regression test results obtained an R-value of 0,813 which shows a strong relationship, while the R2 value is 66.1%. Conclusion in this study is 32 kDa outer membrane proteins of K. pneumoniae acts as a bacterial adhesin.